Chemically Unprecedented Biocatalytic (AuaG) Retro‐[2, 3]‐Wittig Rearrangement: A New Insight into Aurachin B Biosynthesis. Issue 16 (10th September 2014) - Katsuyama, Yohei; Li, Xu‐Wen; Müller, Rolf; Nay, Bastien
Abstract AuaG is flavin‐dependent monooxygenase responsible for the conversion of aurachin C to aurachin B, a reaction thought to resemble semipinacol migration of the farnesyl substituent. A study of the substrate tolerance of AuaG reveals that it has the peculiar ability to oxidise short‐chain analogues of aurachin D. Unexpectedly, a novel retro‐[2, 3]‐Wittig rearrangement was observed with an isoprenyl substrate analogue, thus leading to the 1, 1‐dimethylallyl ether. Additionally, we found that saturated‐chain analogues of N‐oxidised aurachin C were not transformed by the C3→C4 semipinacol reaction, as might have been expected for such substrates. Based on this and the unique retro‐[2, 3]‐Wittig rearrangement, we discuss an alternative biosynthetic route for the conversion of aurachin C to aurachin B.